PERAN MEKANISME CORPORATE GOVERNANCE SEBAGAI PEMODERASI PRAKTIK EARNING MANAGEMENT TERHADAP NILAI PERUSAHAAN - Ridwan, Mochammad; Gunardi, Ardi (TRIKONOMIKA, 2013)
This study aims to determine how the effect of earnings management on firm value is moderated by the role of corporate governance mechanisms consisting of an outside independent director, institutional ownership , managerial ownership , audit committees , and the classification of public accounting firms ( KAP ) . In this study, the population of the entire company is listed on the Indonesia Stock Exchange totaling 111 companies , but only 103 of the 111 companies that companies used in this study . To find out how the effect of earnings management on firm value is moderated by the role of corporate governance mechanisms using Moderated Regression Analysis . The results prove that the earnings management significantly influence the value of the company . Institutional ownership , managerial ownership , and the classification of KAP is moderating variables influence earnings management relations while independent directors and audit committees is not a moderating variable.